Gene Expression Profile Analysis of Human Epidermal Keratinocytes Expressing Human Papillomavirus Type 8 E7 - Xianzhen Chen; Ma Li; Yi Tang; Yi Tang; Qichang Liang; Chunting Hua; Huiqin He; Yinjing Song; Hao Cheng (Frontiers Media S.A., 2022)
Background: Human papillomavirus type 8 (HPV8) has been implicated in the progress of non-melanoma skin cancers and their precursor lesions. The HPV8 E7 oncoprotein plays a key role in the tumorigenesis of HPV-associated cutaneous tumors. However, the exact role of HPV8 E7 in human epidermal carcinogenesis has not been fully elucidated.Methods: To investigate the potential carcinogenic effects of HPV8 E7 on epithelial cells, we used RNA-sequencing technology to analyze the gene expression profile of HPV8 E7-overexpressed normal human epidermal keratinocytes (NHEKs).Results: RNA-sequencing revealed 831 differentially expressed genes (DEGs) between HPV8 E7-expressing NHEKs and control cells, among which, 631 genes were significantly upregulated, and 200 were downregulated. Gene ontology annotation enrichment analysis showed that HPV8 E7 mainly affected the expression of genes associated with protein heterodimerization activity, DNA binding, nucleosomes, and nucleosome assembly. Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis revealed that overexpression of HPV8 E7 affected the expression of gene clusters associated with viral carcinogenesis and transcriptional misregulation in cancer and necroptosis signaling pathways that reportedly play crucial roles in HPV infection promotion and cancer progression. We also found the DEGs, such as HKDC1 and TNFAIP3, were associated with epigenetic modifications, immune regulation, and metabolic pathways.Conclusion: Our results demonstrate that the pro-carcinogenic effect of HPV8 expression in epithelial cells may be attributed to the regulatory effect of oncogene E7 on gene expression associated with epigenetic modifications and immune and metabolic status-associated gene expression. Although our data are based on an in vitro experiment, it provides the theoretical evidence that the development of squamous cell carcinoma can be caused by HPV.